2005
DOI: 10.1111/j.1528-1167.2005.29604.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lasting Antiepileptic Effects of Levetiracetam against Epileptic Seizures in the Spontaneously Epileptic Rat (SER): Differentiation of Levetiracetam from Conventional Antiepileptic Drugs

Abstract: Summary:Purpose: Some evidence suggests that levetiracetam (LEV) possesses antiepileptogenic characteristics. The purpose of this study was to investigate the time course of seizure protection by LEV compared with that of phenytoin (PHT), phenobarbital (PB), valproate (VPA), and carbamazepine (CBZ) in the spontaneously epileptic rat (SER). The SER is a double mutant (tm/tm, zi/zi) showing both tonic convulsions and absencelike seizures.Methods: The effect of single (40, 80, and 160 mg/kg, i.p.) and 5-day (80 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…In addition, when LRV is administered daily in SERs for 5 days, inhibitions of seizures are gradually increased with administration day. The inhibitory effects are unusually long-lasting; suppressive effects on convulsion are still apparent 3 days after the final drug injection, and those on absence-like seizures persist more than 6 days after termination of the administration (57). However, such unusually long effects are not observed in SERs treated with phenytoin, valproate, carbamazepine, or phenobarbital when these AEDs are administered to SER in a manner similar to LEV (Fig.…”
Section: Antiepileptic Effects Of Lev In Sersmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, when LRV is administered daily in SERs for 5 days, inhibitions of seizures are gradually increased with administration day. The inhibitory effects are unusually long-lasting; suppressive effects on convulsion are still apparent 3 days after the final drug injection, and those on absence-like seizures persist more than 6 days after termination of the administration (57). However, such unusually long effects are not observed in SERs treated with phenytoin, valproate, carbamazepine, or phenobarbital when these AEDs are administered to SER in a manner similar to LEV (Fig.…”
Section: Antiepileptic Effects Of Lev In Sersmentioning
confidence: 91%
“…A single administration of LEV in SERs inhibits both absence-like seizures and tonic convulsions with an unusually long latency and prolonged effects (57). In addition, when LRV is administered daily in SERs for 5 days, inhibitions of seizures are gradually increased with administration day.…”
Section: Antiepileptic Effects Of Lev In Sersmentioning
confidence: 91%
See 1 more Smart Citation
“…3 panel a). This dose of phenytoin was previously shown to reduce acute or spontaneous seizures in rodents within 2 h after a single drug administration [31,32].…”
Section: Pharmacological Treatmentsmentioning
confidence: 96%
“…At doses comparable to those used in this study, PHT was found to attenuate tonic-clonic seizures and wild running in rodents following global cerebral ischemia, demonstrated anticonvulsant potency by the MES test, and reduced audiogenic seizures (AGS) and significantly decreased the number of tonic convulsions in the SER. [31][32][33][34] Unlike ETX, PHT has proven ineffective in elevating minimal electroshock seizure threshold, did not protect against metrazol-induced seizures, and did not affect the absence-like seizures in SER. 32,33 In our model, both ETX and PHT significantly attenuated NCS following TBI.…”
Section: Discussionmentioning
confidence: 99%